Adaptive Marketing Strategy for Sustainable Competitiveness: The Role of Digital Transformation and Innovation Resilience - Abbas, Muchlis (Golden Ratio of Community Services and Dedication, 2026)
This study aims to explore the interrelationship between adaptive marketing strategy, digital transformation, and innovation resilience in achieving sustainable competitiveness in the contemporary digital economy. Grounded in the theoretical perspectives of dynamic capabilities and organizational resilience, this research employs a qualitative approach through an integrative literature review of 40 peer-reviewed studies published between 2015 and 2025. The method involved systematic data collection from academic databases, thematic synthesis, and interpretive analysis to identify recurring concepts, patterns, and frameworks relevant to adaptive marketing. The findings reveal that digital transformation functions as a strategic catalyst that enhances marketing adaptability through technological integration, data-driven decision-making, and customer-centric innovation. Meanwhile, innovation resilience emerges as a sustaining force that enables firms to preserve creativity and strategic continuity amid turbulence, thereby reinforcing adaptive marketing capabilities. The results further demonstrate that adaptive marketing strategy acts as a mediating mechanism connecting digital transformation and innovation resilience to sustainable competitiveness. This study concludes that the synergy among these constructs generates a continuous cycle of learning, adaptation, and renewal, positioning adaptive marketing as a dynamic capability essential for long-term survival and ethical growth. The research contributes to advancing the conceptual understanding of marketing adaptability and provides managerial insights into integrating technological agility, resilience, and sustainability into strategic marketing practices.